EFFECT OF REGIONAL ORIGINAL INCOME, BALANCED FUNDS, CAPITAL EXPENDITURE AND HUMAN DEVELOPMENT INDEX ON ECONOMIC GROWTH - Lia Febriana Karwahningrum; Eko Triyanto (Berkala Akuntansi dan Keuangan Indonesia, 2021)
This study aims to analyze the effect of Local Own Income, Balanced Funds, Capital Expenditures and Human Development Index on Economic Growth in Surakarta City 2010-2017.The method of determining the sample used in research is the saturated method. The analytical methodology used in the study was carried out with multiple regression with the SPSS 25 program. The results obtained from the research showed that local revenue, balanced funds and capital expenditures did not partially affect economic growth in the city of Surakarta during the 2010-2017 period. Meanwhile, the Human Development Index has a partial effect on Economic Growth in the City of Surakarta during the 2010-2017 period.